(untitled) (Research, Society and Development, 2022)
Objective: to highlight the findings in the literature regarding the risk factors associated with the persistence of gestational syphilis. Methodology: this is an integrative review, based on the following guiding question: what are the risk factors associated with gestational syphilis and how do they interrelate for its persistence? For this, PubMed, MedLine and Scielo databases were consulted. Results: the main risk factors found for the persistence of gestational syphilis were: schooling, socioeconomic status, inadequate prenatal care, reduced number of consultations, young age, brown skin, non-use of contraceptive methods, inadequacy of treatment in general and of the sexual partner. Final Considerations: the importance and need for public policies aimed at the most affected public is perceived, to reduce the number of cases of gestational syphilis. Therefore, the Basic Health Unit, as a gateway for the maternal population, must, through the Health Agents, intensify the search for pregnant women and their sexual partners, in order to provide them with quality treatment.